Forecasting the Demand of Clinical Pharmacist Workforce in Future Fifteen Years (2016-2030) at all Healthcare institutions in Saudi Arabia - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objectives: The workforce of clinical pharmacist is one the elements of pharmacy strategic plan in Saudi Arabia. The purpose of this study is to explore the demand for clinical pharmacist’s workforce in fifteen years (2016-2030) at Ministry of Health hospitals and primary care centers, and all Non-Ministry of Health hospitals in Saudi Arabia. Methods: It is a prospective analysis of fifteen years (2016-2030) of health care provider hospital and MOH primary care centers projecting demand of clinical pharmacists in the future. All data were derived from Ministry of health statistical Year Books. It included current and future demand for clinical pharmacist workforces at hospitals in Kingdom of Saudi Arabia. The type of hospital included having bed capacity of 50-1500 beds with Adults public hospitals, pediatrics and maternity hospitals, Psychiatric hospitals, Diabetic centers, Cardiology centers, Oncology Centers, Renal Dialysis Centers, and Medical cities. All calculations were based on MOH clinical pharmacist workforce standards of hospitals. The calculations were per each region for a total of twenty-one regions for MOH hospital and primary care centers, the expected number of clinical pharmacist requirement in the coming years 2016-2030 were estimated per each sector across Saudi Arabia. Result: The total numbers of hospitals were 466 in the kingdom of Saudi Arabia, 274 (58.8%) Ministry of Health hospitals, 152 (32.6%) private hospitals, and 40 (8.6%) non-MOH governmental hospitals. Over the eleven years, the average number of hospitals were (423.45) with a range number of (384-467), and the total number was (467).The total average demand of clinical pharmacists at MOH hospitals by the year 2030 will be (6,018.96) with range (5,020.20-7,132.26) while the average total demand of clinical pharmacists at MOH primary care centers by the year 2030 will be (2787.55) with range (2,325.00-3,303.16). The total requirement of a clinical pharmacist in all sectors by the year 2030 will be (12,077.88) with range (8,501.28- 12,077.88). Conclusion: The MOH hospitals and primary care centers sectors will be with the highest demand for clinical pharmacists in the future. Targeting for more graduated clinical pharmacist from the college of pharmacies, opening new clinical pharmacist jobs, and implementation of new vision of pharmacy practice by 2030 is required in Saudi Arabia.
Keywords: Clinical pharmacist; Workforces; Ministry of health; Saudi arabia